Economic MPC for online least costly energy management of hybrid electric vehicles. (September 2020) - Pozzato, Gabriele; Müller, Matthias; Formentin, Simone; Savaresi, Sergio M.
Abstract: In this work, the problem of online energy management of hybrid electric vehicles is addressed. A least costly objective function accounting for battery energy consumption and aging, and for the auxiliary power unit fuel consumption and noise emissions is considered. In this scenario, all the cost terms are expressed as monetary variables. This allows to assess the economic effectiveness of the proposed hybrid powertrain solution. Therefore, the online energy management policy is computed relying on the economic model predictive control framework. Some dissipativity properties for steady-state and periodic operation of the system under investigation are proved. Therefore, some results for close to optimum convergence of the economic model predictive control are provided. An electric bus case-study is illustrated in detail to show the performance of the proposed online management strategy.